Glacial chronology and topographic controls in the Tsambagarav Massif, western Mongolia: Insights from 10Be dating - Khandsuren, Purevmaa; Seong, Yeong Bae; Rhee, Hyun Hee; Demberel, Otgonbayar; Yu, Byung Yong (Pergamon Press Ltd., 2026)
The Tsambagarav Massif in the Mongolian Altai preserves a detailed record of glacial fluctuations from the Late Pleistocene to the present. Using geomorphological mapping, Be-10 surface exposure dating, equilibrium line altitude (ELA) reconstructions, and geomorphometric analysis, we reconstruct the extent, timing, and dynamics of glacier advances across the massif. Our results indicate that the maximum glacial advance in the Ulaan Am (southwestern) Valley predated global Last Glacial Maximum (gLGM), occurring during MIS 3 (similar to 40 ka), with a subsequent readvance between similar to 31 and 21 ka. In contrast, other glaciers, including the Tsagaan Seer (southwestern) and Yamaat (northern), reached their maximum positions broadly synchronous with the gLGM (similar to 26.5-19 ka). Furthermore, the Bituu Ereg (eastern) Valley records a significant Late Glacial expansion at similar to 15.4 ka. Following these advances, glaciers retreated abruptly and the massif was completely deglaciated by the mid-Holocene thermal maximum. Glaciers subsequently reformed during the Neoglacial (similar to 6 ka) and responded sensitively to centennial-scale climate variability, including advances during the Little Ice Age (LIA) and rapid retreat under recent warming. Modern and Late Pleistocene ELAs exhibit a clear regional rise from the northwest toward the southeast across the Altai Mountains. The magnitude of Late Pleistocene ELA depressions follows the same orientation, reflecting an increased glacial sensitivity to climatic shifts in more arid environments. Throughout the massif, glacial distribution and magnitude have been consistently modulated by topographic controls rather than climate alone. Specifically, northern and eastern slopes supported the most extensive ice cover; northern glaciers were sustained by reduced solar radiation through topographic shading, while eastern glaciers were possibly driven by enhanced snow accumulation from westerly wind drift and the structural eastward tilt of the massif. These findings highlight the critical interplay between regional climate and local terrain in shaping glacial histories in arid high-mountain environments, contributing to a broader understanding of Quaternary glaciation across Central Asia.